Source-sink relations and kernel weight in maize inbred lines and hybrids : responses to contrasting nitrogen supply levels - Hisse, Ignacio R.; D'Andrea, Karina Elizabeth; Otegui, María Elena (Elsevier, 2019)
Maize (Zea mays, L.) kernel weight (KW) is regulated by the source-sink relationship at the early grain-filling period, when potential kernel size is defined, and at the effective grain-filling period, when final KW is established. The relative importance of each period is expected to depend upon the occurrence or not of environmental restrictions to plant growth. The objective of this study was to analyze the effect of nitrogen (N) availability on KW determination in two different groups of genotypes (inbreds and hybrids) when it is caused by changes in the source-sink relationship at mentioned periods. Six inbred lines of different genetic background and their F1 derived hybrids were tested in the field under two contrasting soil N levels (N0: low; N1: high). Almost all evaluated traits had greater mean values (P < 0.001) at N1 than at N0 level, except the plant growth rate per kernel during the critical period for kernel set (PGRCP kernel−1). However, the magnitude of the response to increased N was considerably higher for hybrids than for inbreds. Under contrasting N availability, plant growth during grain filling (PGGF) was the main determinant of increments registered in the source-sink ratio during this stage (i.e. PGGF kernel−1), and KW was chiefly associated with this ratio (r2 ≥ 0.50, P < 0.001). By contrast, the association between KW and PGRCP kernel-1 was important only at N1, and more robust for hybrids (r2 = 0.61, P < 0.001) than for inbreds (r2 = 0.34, P < 0.001). The uncoupling between both source-sink ratios observed at N0, as a result of a decreased post-flowering growth in this treatment, was responsible for differences in KW response to the PGRCP kernel−1 detected between N levels. The KW of inbreds was almost unaffected by mentioned N effects on the analyzed source-sink ratios, a trend attributed to negative inbreeding depression effects on traits controlling seed expansion. These differential responses between genotypic groups should be considered in breeding programs targeting KW increase.